TTRV30M oligomeric aggregates inhibit proliferation of renal progenitor cells but maintain their capacity to differentiate into podocytes in vitro - Moreira, L. (2014)
Publicado em: The Proceedings of the XIIIth International Symposium on Amyloidosis, May 6-10, 2012, Groningen, The Netherlands